SCREENING OF IMMUNOMODULATORY EFFECT OF SHATAPUTI ABHRAK BHASMA- AYURVEDA'S RASAYAN - Yogesh Laxman, *Tamhankar; Devyani Deodatta, Bhadlikar; Tryambaklal, Mehta Mahendra; Nilesh, Suryawanshi; Ekta, Tomar (International Journal of Ayurveda and Pharma Research, 2015)
Rasashastra, one of the branches of Ayurveda, deals with the pharmacological aspects of drugs, some of which have unique attributes. These unique attributes need to be validated and explored using the scientific and technological advances of todays world, which shall open up new avenues for drug processing, development and therapeutics in Ayurveda.Abhrak Bhasma is one of the drugs of Rasashastra having some peculiar attributes. Acharyas have mentioned Shataputi and Sahastraputi Abhrak Bhasma which are indeed unique attributes of Abhrak. Shataputi Abhrak Bhasma is regarded as a Rasayan, as given in Rasa Tarangini, which says Abhrak Bhasma given 20-100 Putas (incinerations) helps eliminate ailments, when given 100-1000 Putas acts like a Rasayan.Review of the current literature available on Rasayanas indicates that Anti-oxidant and Immunomodulation are the most studied activities of the Rasayan drugs. The effect Immunomodulation has on the human body can be compared to some extent with the effect of Rasayan dravyas, given in various Classical texts. In view of this correlation, Shataputi Abhrak Bhasma was subjected to Invitro screening to assess its Immunomodulatory effect using the Nitroblue Tetrazolium (NBT) assay. The results were self conclusive and indicated that Shataputi Abhrak Bhasma brings about stimulation of Leucocytes in concentration dependent manner. 5% and 10 % solutions of Shataputi Abhrak Bhasma stimulated 93% and 93.5% leucocytes respectively, which is an indicator of highly significant phagocytic activity. Thus, the study revalidates the reference of Shataputi Abhrak Bhasma as a Rasayan and hence also establishing it as an Immunomodulator.